The Inlfuence of Internal Control on Good Corporate Governance in Pt Pos Indonesia (Persero) Bandung City - Azka Salsabila (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2023)
This study aims to determine the effect of internal control on good corporate governance. The factors tested in this study are the independent variable is internal control, while the dependent variable is good corporate governance. The research method used is the verification method. The population in this study is the internal auditor at the Internal Supervisory Unit (SPI) at PT Pos Indonesia (Persero) Bandung City, amounting to 36 employees. The sampling technique used is a non-probability sampling technique with a total sampling technique, so that the number of samples is 36 employees. The analytical method used is simple linear regression analysis using the SPSS Version 25.00 program. The results of the study indicate that internal control and good corporate governance are included in the fairly good category. In addition, the results of hypothesis testing show that internal control has an effect on good corporate governance at PT Pos Indonesia (Persero) Bandung City. The magnitude of the influence of internal control in contributing to the influence of good corporate governance is 44.9%.